2016
DOI: 10.1051/matecconf/20178702021
|View full text |Cite
|
Sign up to set email alerts
|

Emission Treatment towards Cold Start and Back Pressure in Internal Combustion Engine against Performance of Catalytic Converter: A Review

Abstract: Abstract. Nowadays, regulation for the vehicles emissions has becoming more stringent in order to reduce the effect of pollutant gases that was being released by the vehicles exhaust. The development of catalytic converter is to resolve the pollution emission aspect . There are lots of improvements done by the researchers towards improving catalytic converter, yet there are still key issues which give negative impact to the environment. One of the problems that are being concern by among of researchers is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The need to take into account emissions from the cold start phase has been noticed not only in Europe but also worldwide. The authors of the articles [18,26] pointed out the importance of the cold start issue as well as the necessity of further improvement of exhaust after-treatment systems. Whereas, the authors of the publications [8,10,11] suggested that NO x emission should be an issue addressed in subsequent updates of EU regulations.…”
Section: Introductionmentioning
confidence: 99%
“…The need to take into account emissions from the cold start phase has been noticed not only in Europe but also worldwide. The authors of the articles [18,26] pointed out the importance of the cold start issue as well as the necessity of further improvement of exhaust after-treatment systems. Whereas, the authors of the publications [8,10,11] suggested that NO x emission should be an issue addressed in subsequent updates of EU regulations.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to find a three-way catalytic converter, which, on the one hand, will allow a significant reduction in the concentration of toxic exhaust components starting from the lowest possible temperature of the exhaust downstream from the turbine, and on the other hand, will have low exhaust gas flow resistance. Increasing the flow resistance raises backpressure of gases in the exhaust system, which in turn increases the pumping losses, reducing the effect of energy recovery in the cylinders of the additional expansion of the five-stroke engine [27].…”
Section: Research Problem and Aim Of Workmentioning
confidence: 99%
“…With the rapid development of China's economy, people's living standards are also improving, and private cars have gradually entered the family. However, traditional fossil fuel resources such as oil are limited, and their combustion will emit greenhouse gases (GHG) and harmful substances [1,2] and affect the environment and climate [3] . A series of problems, such as energy shortage, environmental pollution and climate warming, brought by the traditional petrol-powered vehicles with oil or diesel as the main fuel, have also become the public concerns [4] .…”
Section: Introductionmentioning
confidence: 99%